Preparation of xylo-oligosaccharides and its effect on invitro proliferation of probiotics - LI Yan-li; XU Shao-chun; LIU Yong; YANG Hui-ling; XU Yao-xing (浙江大学学报. 农业与生命科学版, 2011)
Xylo-oligosaccharides (XOS) from corncob were prepared by microwave digestion and a commercial endoxylanase hydrolysis. "One-factor-at-a-time" method was applied to optimize the reaction parameters for improving XOS concentration, and the effect of obtained XOS on in vitro proliferation of probiotics (Bacillus subtilis and Lactobacillus) was studied. The results showed that the optimal conditions were as follows: microwave digestion pressure of 1.6 Mpa and microwave digestion time of 5 min, endoxylanase concentration of 140 U·g-1 and enzymatic reaction time for 6 h. Under optimal conditions, hydrolysis of alkali pretreated corncob powder using microwave digestion and endoxylanase produced 82.5% of XOS in the hydrolyzate, equivalent to 11.02 g·L-1 XOS. In vitro proliferations of Lactobacillus and B. subtilis were activated by 311% and 183% with the addition of 0.2% and 0.4% XOS, respectively, however their growths were inhibited with increasing the amount of XOS addition.